2020
DOI: 10.1159/000506393
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Use of Intra-Aortic Balloon Pump Support Reduced 30-Day Mortality in a Population with LVEF >35% and High Surgical Risk after Coronary Artery Bypass Graft Surgery

Abstract: Introduction: The intra-aortic balloon pump (IABP) is used to prevent complications after coronary artery bypass grafting (CABG) surgery, although some results are controversial and basal ventricular function may play a role. This study assessed the benefit of preoperative use of IABP, as stratified by the ventricular function, in a population submitted to high-surgical-risk CABG. Methods: Patients > 18 years old, with multiple coronary artery disease and thus candidates for CABG, were included. Cardiogenic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…On the other hand, the multivariable logistic regression analysis shown that the risk factors for in‐hospital mortality were preoperative plasma creatinine and CABG time, OR = 5.74 and OR = 1.02, respectively ( p < .05). All these data are consistent with another previous studies 11–13 thus deserving special attention.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the multivariable logistic regression analysis shown that the risk factors for in‐hospital mortality were preoperative plasma creatinine and CABG time, OR = 5.74 and OR = 1.02, respectively ( p < .05). All these data are consistent with another previous studies 11–13 thus deserving special attention.…”
supporting
confidence: 93%
“…Regarding secondary endpoints, the study of Samadi et al shows that patients with left ventricular ejection fraction (LVEF) ≤ 35% had longer in‐hospital length of stay compared to patients with LVEF > 50% (median [interquartile range]: 10 [8–13] and 8 [7–10] days, respectively [ p = .04]), already seen in previous reports 9,11,13,18 . This outcome may be explained by the time required for accomplishing the IABP weaning as well as the time for recovery after the operation, a feature observed in almost all similar studies, thus giving an external validation to the results obtained in the study.…”
mentioning
confidence: 60%
“…On the other hand, the multivariable logistic regression analysis shown that the risk factors for in-hospital mortality were preoperative plasma creatinine and CABG time, OR=5.74 and OR=1.02, respectively (p<0.05). All this data consistent with another previous studies (11,12,14) thus deserving special attention.…”
supporting
confidence: 92%
“…Regarding secondary endpoints, the study of Samadi et al shows that patients with LVEF [? ]35% had longer in-hospital length of stay (LOS) compared to patients with LVEF >50% (median [IQR] 10 [8-13] days and 8 [7][8][9][10] days respectively [p=0.04]), already seen in previous reports (9,11,14,18). This outcome may be explained by the time required for accomplish the IABP weaning as well as the time for recovery after operation, a feature observed in almost all similar studies, thus giving an external validation to the results obtained in the study.…”
supporting
confidence: 57%
“…Although some meta-analyses suggest a benefit in mortality and MACCE, the prophylactic pre-operative insertion of IABP in patients undergoing high-risk coronary artery bypass grafting (CABG) remains controversial [18][19][20][21].…”
Section: Prior To High-risk Coronary Artery Bypass Graft Surgerymentioning
confidence: 99%